Topical anti-aging agents: state-of-the-art review - Prakoeswa, Flora Ramona Sigit; Maharani, Faradiba; Satria, Yohanes Aditya Adhi; Awanis, Ghina Shabrina; Febrianty, Astrida Fesky (Universitas Gadjah Mada, 2023)
Skin aging can be divided into intrinsic and extrinsic aging. Even though it is inevitable, symptoms of skin aging are a common concern for patients. As a result, there is a surge in the making of anti-aging cosmeceuticals. However, there is a lack of evidence-based data to support the usage of topical preparations as anti-aging treatments. Therefore, further studies are needed to explore topical treatment options for skin aging. This literature review discusses the mechanism of commonly used topical anti-aging agents and their adverse reactions.